PROBLEMATIKA SISWA DAN GURU DALAM PEMBELAJARAN DI KELAS 2 SDN 1 SEMANGKAK - Al Ghadafi, Muhammer (Universitas Sebelas Maret, 2022)
This research aims to analyze the main problems faced by teachers and students in 2nd grade elementary school learning, as well as formulating effective strategies to overcome these challenges. Special focus is given to aspects such as students' limited attention, differences in learning abilities, teacher mastery of material, students' social aspects, parental involvement, and evaluation of student progress. The learning process in grade 2 elementary school involves complex problems that affect cognitive, social and environmental aspects. In this context, a deep understanding of the challenges and learning needs at this level becomes important. This research was conducted to provide in-depth insight into the obstacles faced and design strategies that can increase learning effectiveness. This research uses a qualitative approach with data collection techniques through literature study and content analysis. The proposed strategy involves the development of innovative teaching methods, implementation of learning differentiation, use of technology, collaboration between teachers, students, and parents, as well as ongoing training for teachers.